2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23117
|View full text |Cite
|
Sign up to set email alerts
|

Textual Appropriation and Attribution in Engineering Theses and Dissertations: An Exploratory Study

Abstract: Currently he is an engineering and applied sciences librarian at Western Michigan University Libraries. His work has appeared in Science and Engineering Ethics, College & Undergraduate Libraries, Issues in Science and Technology Librarianship, Internet Reference Services Quarterly, and Reference & User Services Quarterly. His research interests include plagiarism and research skills training in engineering graduates and undergraduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Studies into the techniques that different communities use to distinguish authors' original contributions are closely related to the former question about what needs attribution. Whether about medium (e.g., Eisner & Vicinus, 2008) or discipline (e.g., Eckel, 2014;Jamieson, 2008), these studies are centered around what kind of information is considered collectively shared information, which can be used without attribution, and what is considered "owned" (Haviland & Mullins, 2009), which needs attribution. Style manuals and handbooks tend to refer to collectively shared information as common knowledge, which Amy England (2008) argued is often implicitly defined in these references as "an established, static set of facts" (p. 109).…”
Section: Current Writing Studies Scholarship In Attribution Practice and Instruction Is Underscored By Two Central Questions: What Needs mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies into the techniques that different communities use to distinguish authors' original contributions are closely related to the former question about what needs attribution. Whether about medium (e.g., Eisner & Vicinus, 2008) or discipline (e.g., Eckel, 2014;Jamieson, 2008), these studies are centered around what kind of information is considered collectively shared information, which can be used without attribution, and what is considered "owned" (Haviland & Mullins, 2009), which needs attribution. Style manuals and handbooks tend to refer to collectively shared information as common knowledge, which Amy England (2008) argued is often implicitly defined in these references as "an established, static set of facts" (p. 109).…”
Section: Current Writing Studies Scholarship In Attribution Practice and Instruction Is Underscored By Two Central Questions: What Needs mentioning
confidence: 99%
“…For example, studies have shown that researchers in STEM are less concerned about word-for-word matches without quotation than in other fields (Buranen & Stephenson, 2009;Eckel, 2014), "plac[ing] a higher priority on the attribution of ideas than the attribution of words" (Eckel, 2014, p. 2). Such studies suggest that disciplinary distinctions often fall around the values of using one's own words and the importance of quotation; text-centered disciplines tend to value quotation in ways that other research forms do not.…”
Section: Attribution and Common Knowledge Across The Curriculummentioning
confidence: 99%
“…Previous studies have demonstrated an imbalance in education and academic integrity awareness across the globe [6], finding disproportionate amount of integrity work for the same size of population [8], as well as unmatched opinions from geographic locations when interpreting dishonest practices [9]. These examples highlight the influence of demographics on students' academic honesty awareness.…”
Section: Introductionmentioning
confidence: 93%
“…Understanding the root cause for academic dishonesty can facilitate how to successfully address these behaviors [4], especially when they stem from lack of awareness and know-how in specifying references appropriately [4]. Field of study [6] and culture background [4] have been correlated with the likelihood of plagiarism [3], [4]. Students who lack comprehension necessary to follow a class and feel uncomfortable asking critical questions, or cannot comfortably express themselves may feel more inclined towards dishonesty, being non-native English speakers with poor study skills the group with the highest risk [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation